Monsters, Myths, and Masculinities in Boscán’s 'Respuesta a Don Diego de Mendoza' - Paul Joseph Lennon (Modern Languages Open, 2023)
Renowned for its portrayal of conjugal love, Juan Boscán’s 'Respuesta a Don Diego de Mendoza' also makes use of lesser-studied mythological references to the androgyne, harpies, and King Phineus. Through a consideration of these references in context, namely the poetic voice’s description of the couple’s union and the rewrite of Petrarch’s “Passer mai solitario in alcun tetto”, I expose hitherto unexplored tensions resulting from the complex and often contradictory strands of contemporary masculinity that fed into the radical reshaping of gender constructs among the nobility due to the rise of the courtier. In particular, I show how Boscán’s social commentary and originality in advocating for a conjugal model also had the potential to spark masculinity-related anxieties, which take the form of monstrosities, among his noble readership during this period of transition.